Effects of diffusion on energy transfer in solution using a microsecond decay time rhenium metal–ligand complex as the donor - Kuśba, Józef (Chem Phys Lett, 2000)
We used resonance energy transfer and frequency-domain fluorometry to measure slow donor to acceptor diffusion in viscous media. The frequency-domain RET data were analyzed using a new numerical algorithm for predicting the donor intensity decay in the presence of diffusion occurring within the donor decay time. By the use of a rhenium metal–ligand complex as a microsecond decay time donor we were able to measure mutual donor-to-acceptor diffusion coefficients as low as 2 × 10(−8) cm(2)/s. The availability of microsecond decay time luminophores and appropriate theory suggests the use of diffusion-enhanced energy transfer for measurement of diffusive processes and structural dynamics in biological systems.